Keefektifan Promosi Melalui Tiktok Untuk Produk Skincare Erto’s - Rista Sugiarti; Yesi Amanah; Indri Nova Yulianti (Yayasan Literasi Sains Indonesia, 2022)
The Government's decision to implement Large-Scale Social Restrictions (PSBB) in April 2020 had a broad impact on the production process, distribution, and other operational activities, thereby changing consumer consumption patterns for online transactions. The use of social media is of course supported by the development of social media users in Indonesia. Currently the most popular social media among Indonesians is TikTok. The TikTok app is a social media app where users can share short music videos. Application research company Sensor Tower has again released a report on the most downloaded non-game applications for August 2020. This edition named TikTok as the best-selling application with a total of more than 63.3 million downloads on iOS and Andoid devices. The number is up 1.6 percent from the same period last year. Erto's Beauty Care utilizes the social media application TikTok in promotional activities to support its business. The purpose of his study was to determine the effect of promotion effectiveness on consumer purchase intentions for Erto's Beauty Care products using the TikTok application. The type of research used is descriptive quantitative. Based on the results of simple linear regression analysis, the results of the regression coefficient are positive numbers, which means the direction of the X and Y variables is positive, i.e. if the effectiveness of promotion in the TikTok application is higher, the consumer's purchase intention is also higher for Erto's Beauty Care products. From the results of the partial test or t test, it can be concluded that the effectiveness of the promotion has an effect on consumers' purchase intentions for Erto's BeautyCare products.